THE EMERGENT ROLE OF NURSING AND NURSING ROBOTS-COMPREHENSIVE REVIEW - Adel Abdullah Alami, Aeidha Owaid Jubier Alsulami, Marzog Naga Alotaibi, Ashwag Saad Albishi, Latifa Sayer Aldhafeeri, Abdulaziz Ahmed Hassan Alzahrani, Nawal Obaid Ali Alanazi; Hussain Hamad Hakami, Sharifah Hudayban Alharbi, Saleh Motlaq Ibrahim Alotibi, Motaz Hadi Abbas Hakami, Abdullah Naghimash Alharbi, Afnan Othman Omar Hawsawi, Ali Mohmmed Abdo Homedi (Chelonian Research Foundation, 2022)
This research examines the complex relationship between assistive robotics and nursing, examining how they might transform healthcare delivery while tackling a number of issues. The attitudes and expectations of patients, the elderly, nurses, and caregivers all play a significant role in user approval. Geographical and cultural disparities exacerbate acceptance issues and highlight the necessity for customized design strategies. To ensure safe and efficient human-robot interaction, technological difficulties such as autonomy, motion system design, and interface usability demand creative technical solutions. The deployment and operation of these robots must be governed by strong legal and ethical frameworks, especially with regard to data security and liability concerns. Notwithstanding these obstacles, global research initiatives are propelling advancements in the fields of nursing and assistive robots. Adoption can be facilitated, and obstacles overcome with the help of innovations in stakeholder involvement, interdisciplinary collaboration, and human factors engineering. An understanding of "design for excellence" and using informed design approaches are essential to producing robotic systems that are acceptable, efficient, and usable. Nursing and assistive robots have the power to revolutionize healthcare delivery by tackling these issues, considering the opinions of stakeholders, and improving patient outcomes as well as caregiver assistance and overall quality of care.